APPLICATION OF GREEN CHEMISTRY ORIENTED ALTERNATIVE FUEL E-MODULE - Hamidatu Ramdhaniah; Sari Sari; Ida Farida (UIN Sunan Gunung Djati Bandung, 2021)
The purpose of this research was to apply an e-module of alternative fuel oriented to green chemistry. The method used was pre-experiment. The data sources in this study came from 40 students of the second semester of the Chemistry Education Study Program who enrolled in General Chemistry II using worksheets instrument and from observers who used observation sheets by observing student activities during the learning process. The application of e-module with green chemistry oriented alternative fuel in this study used a scientific learning process that ran very well because in each stage all students play an active role during the learning process. This was evidenced by the average results of student activity implementation which are 86.83% with very high category. The results obtained were due to the teaching material media in the form of e-module with green chemistry oriented alternative fuels plays a role in the active learning process.